1993
DOI: 10.1109/77.233349
|View full text |Cite
|
Sign up to set email alerts
|

Effects of process variables on the properties of YBa/sub 2/Cu/sub 3/O/sub 7-x/ ceramics formed by investment casting

Abstract: An investment casting process has been developed to produce net-shape, superconducting ceramics. In this work, a factorial experiment was performed to determine the critical process parameters for producing cast YBa2Cu3 @ ceramics with optimum properties. An analysis of variance procedure indicated that the key variables in casting superconductive ceramics are the particle size distribution and sintering temperature. Additionally, the interactions between the sintering temperature and the other process paramet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…61 Many researchers (Hooker et al) have manipulated density, porosity and critical current density of fired ceramics choosing four variables: sintering temperature, particle size distribution of YBa 2 Cu 3 O 7x powder, solid loading of the slip and silver dopant level, as shown in Table 7. Analysis of variance results indicated that porosity and density were highly dependent upon particle size distribution, and 15% porosity was increased by sintering at 935 °C for 8 h. 62 Investigation has been made to determine the thermal boundary conditions that exist during the solidification of metallic alloys in IC. Quantitative information about these conditions was used in their research to produce accurate results, and the method used involves application of a new inverse heat conduction method for thermal data recorded during laboratory experiments of aluminium alloy (A413, A356, A319 and commercially pure Al) solidification in IC shell moulds; the resultant heat transfer coefficient (HTC) for the alloy/mould interface was calculated.…”
Section: Introductionmentioning
confidence: 99%
“…61 Many researchers (Hooker et al) have manipulated density, porosity and critical current density of fired ceramics choosing four variables: sintering temperature, particle size distribution of YBa 2 Cu 3 O 7x powder, solid loading of the slip and silver dopant level, as shown in Table 7. Analysis of variance results indicated that porosity and density were highly dependent upon particle size distribution, and 15% porosity was increased by sintering at 935 °C for 8 h. 62 Investigation has been made to determine the thermal boundary conditions that exist during the solidification of metallic alloys in IC. Quantitative information about these conditions was used in their research to produce accurate results, and the method used involves application of a new inverse heat conduction method for thermal data recorded during laboratory experiments of aluminium alloy (A413, A356, A319 and commercially pure Al) solidification in IC shell moulds; the resultant heat transfer coefficient (HTC) for the alloy/mould interface was calculated.…”
Section: Introductionmentioning
confidence: 99%